2012
DOI: 10.1890/es11-00333.1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and structure of soil bacterial communities associated with vultures in an African savanna

Abstract: Abstract. Bird guano has been shown to alter the structure and function of ecological communities.Here we characterize the effects of vulture guano on the phylogenetic structure, taxa richness, and abundance in soil bacterial communities within an African savanna. By altering soil chemistry and nutrient status, vulture guano appears to play a role in influencing the structure of soil bacterial communities. DNA was extracted from soil collected under twenty trees: five African white-backed vulture (Gyps african… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…Proteobacteria dominated both environments as is common for soils worldwide (Janssen 2006), but were significantly overrepresented in patches with their high resource availability. This correlates well with the observation that Proteobacterial abundance increases with total organic carbon from the local to the global scales (Fierer et al 2007;Ganz et al 2012). Furthermore, the overrepresentation of Proteobacteria in carbon-rich soils was associated with the underrepresentation of four major phyla (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Proteobacteria dominated both environments as is common for soils worldwide (Janssen 2006), but were significantly overrepresented in patches with their high resource availability. This correlates well with the observation that Proteobacterial abundance increases with total organic carbon from the local to the global scales (Fierer et al 2007;Ganz et al 2012). Furthermore, the overrepresentation of Proteobacteria in carbon-rich soils was associated with the underrepresentation of four major phyla (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Soil bacterial communities were phylogenetically clustered, as has been repeatedly reported in the literature across biomes (Horner-Devine & Bohannan 2006;Bryant et al 2008;Costello et al 2009;Chong et al 2012;Ganz et al 2012). Using a trait-based approach, here we provide evidence supporting that phylogenetic clustering in soil bacteria can arise from the environmental selection of conserved functional traits either conferring tolerance to environmental stress or competitive abilities.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous theory had suggested that white‐backed vultures ( Gyps africanus ) and lappet‐faced vultures ( Torgos tracheliotos ) might disperse bacteria from carcass sites to their nesting sites and thereby help spread disease, based on anecdotal evidence (Bullock, ), examination of faeces and contaminated water (Lindeque & Turnbull, ; Hugh‐Jones & De Vos, ), and experimental work on anthrax spore passage through vulture digestive tracts (Urbain & Novel, ; Houston & Cooper, ). However, research in Etosha failed to find higher B. anthracis concentrations at vulture nests, perhaps because vultures' acidic droppings produce soil unsuitable for anthrax spores (Ganz et al ., ). Furthermore, during the first 72 h after carcass deposition, if a carcass remains unopened, vegetative cells fail to sporulate, ending the life cycle (Davies, ; Lindeque & Turnbull, ; Hugh‐Jones & De Vos, ).…”
Section: Anthrax: a Case Study In Slow Integrationmentioning
confidence: 99%
“…Although several papers did not describe these parameters, where reported these values were similar across the analyzed sites (protected or modified), indicating a predominance of clayey soils (Table 6.3). the median values of the included studies (Pinto et al 2006;Carvalho et al 2007;Quirino et al 2009;Bresolin et al 2010;Frazão et al 2010;Peixoto et al 2010;Viana et al 2011;Araujo et al 2012;Ganz et al 2012;Mendes et al 2012;Vinhal-Freitas et al 2013;Rachid et al 2013;Rampelotto et al 2013;Rossi et al 2013;Souza et al 2013 …”
Section: Land Use Changes and Soil Propertiesmentioning
confidence: 99%